1980
DOI: 10.1002/1097-4679(198007)36:3<748::aid-jclp2270360325>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

The relative predictive validity of subtle vs. obvious items on the MMPI depression scale

Abstract: To assess the relative predictive validity of subtle and obvious items on the MMPI Depression scale, obvious, neutral, and subtle subscales were formed and used to predict several criterion measures of depression; these included the Beck Depression Inventory, the Depression subscale of the Profile of Mood States, and the Pleasant Events Schedule (N = 209). In general, obvious items were good predictors of all criteria, neutral items overlapped considerably with obvious items, and subtle items generally did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 9 publications
2
24
0
Order By: Relevance
“…S items provided a unique, but small contribution to that criterion. Burkhart et al (1980) looked to several criteria by way of three self-report measures of depression, and D -0 was the best predictor in all cases. Contrary to Gynther et al's results, S items did not provide any unique predictive power; in fact, the D-S subscale had small, but significant negative relationships.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…S items provided a unique, but small contribution to that criterion. Burkhart et al (1980) looked to several criteria by way of three self-report measures of depression, and D -0 was the best predictor in all cases. Contrary to Gynther et al's results, S items did not provide any unique predictive power; in fact, the D-S subscale had small, but significant negative relationships.…”
supporting
confidence: 87%
“…Findings from the present investigation were consistent with those of Burkhart et al (1980) with regard to the validity of S items in the D scale. The D-S items not only failed to provide significantly unique contributions toward the prediction of the depression criteria as indicated by the results of correlations, regressions and the two group analyses, but they were seen to be working in the opposite direction.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, however, a growing body of experimental evidence has been supportive of the more face-valid intuitive-internal approach (e.g., Duff, 1965;Gynther, Burkhart, & Hovanitz, 1979;Burkhart, Gynther, & Fromouth, 1980). Conclusions reached by the authors of these studies have been centered around the assertion that the more subtle portions of empirically derived inventories are in fact unrelated to the traits which they were designed to assess.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Subsequent studies have measured relative contributions of subtle versus obvious items to the Hypomania and Depression subscales (Hovanitz & Gynther, 1980;Burkhart, Gynther, & Fromouth, 1980).…”
mentioning
confidence: 99%
“…The OBD is a measure of depressive symptoms (e.g., I am blue most of the time) that is more appropriate for nonclinical samples than the widely known D scale. Obvious indicators of depression have been shown to be more highly correlated with several criterion measures than the more subtle items (17)(18)(19). Also, unpublished data from a community sample showed that the OBD was correlated with the Beck Depression Inventory (20) similarly in African Americans (r ϭ 0.65) and Caucasians (r ϭ 0.64).…”
Section: Depressive Symptomsmentioning
confidence: 99%